Forming Elitist and Effective Patriotism in Higher Education (Based on the Concept of “Japheth's Power” by Viacheslav Lipinskii) - Паздрій, В. (Київський національний університет імені Тараса Шевченка, 2025)
The relevance of the research. Elitist and effective patriotism, based on the Europeanism of Ukrainians revealed by V. Lypynskii in his concept of “Japheth's Power”, begins with the conscious identification of oneself as a representative of a talented and resourceful nation with a rich past, heroic present and promising future. The founder of the statehood school of Ukrainian historiography offered an innovative vision of patriotism for his time, based on the dynamics of action, motivation for personal achievement for the common good.The concept of elitist, effective, “Japhethian” patriotism significantly modernise and deepen current approaches to patriotic education in higher education, open new areas of research into ways and means of self-development and self-realisation of young people through a patriotic worldview and patriotic activities. This will contribute to the formation of civic and personal responsibility of students for the future of their own state, integration of young people into society through socially useful activities through their own patriotic worldviewThe purpose of the study is to characterise the peculiarities of elitist effective patriotism on the basis of V. Lypynskii's historiosophical vision and to determine its effectiveness in the patriotic education of university students.Conclusions. The education of elitist and effective patriotism is closely related to the humanistic, moral, cultural, aesthetic education of the individual in higher education institutions. The conscious choice of such patriotism becomes natural in the process of self-realisation of the individual as a citizen of modern Ukraine and a carrier of the Ukrainian cultural tradition. Today, the formation of a patriotic outlook of young people is a difficult task for teachers of higher school, as for many years the patriotism of students has been formed according to the post-Soviet, ideological and formal model, often “trouser-like”. This caused patriotic education to be disconnected from the actual priorities of young people's lives, which is why it was not always possible to achieve a high level of civic consciousness among students and their active involvement in public life. Instead, elitist and effective patriotism, which is based on the European nature of Ukrainians revealed by V. Lypynskii in his concept of «Japheth's Strength», begins with a conscious identification of oneself as a representative of a talented and resourceful nation with a rich past, heroic present and promising future. It motivates young people to make a significant contribution to the development of society and the state as a guarantee of personal success and the realisation of their own identities as citizens, patriots, and Ukrainians. Therefore, this type of patriotism can be recognised as effective and promising for Ukraine's post-war recovery after the victory.Keywords: history of Ukraine, patriotic education, elitist and effective patriotism, Japheth's Strength, Japhethianism.

Актуальність. Елітарно-дієвий патріотизм, який базується на розкритій В. Липинським у концепції «Яфетової Сили» європейськості українців, починається зі свідомої ідентифікації себе як представника талановитої й ресурсної нації, яка має багате минуле, героїчне теперішнє і перспективне майбутнє. Засновник державницької школи української історіографії запропонував новаторське для свого часу бачення патріотизму, яке базувалося на динаміці дії, мотивованості на особистісні досягнення заради загального блага. Концепція елітарно-дієвого, «яфетичного», патріотизму суттєво модернізує й поглиблює сучасні підходи до патріотичного виховання у вищій школі, відкриває нові напрямки досліджень шляхів і способів саморозвитку й самореалізації молоді завдяки патріотичному світогляду й патріотичній діяльності. Це сприяє формуванню громадянської й особистісної відповідальності студентства за майбутнє власної держави, інтеграції молоді в соціум шляхом ведення суспільно корисної діяльності, самоствердженню через власне патріотичне світобачення. Мета дослідження – схарактеризувати особливості елітарно-дієвого патріотизму на основі історіософського бачення В. Липинського і визначити його ефективність у патріотичному вихованні студентів ЗВО. Висновки.  Виховання елітарно-дієвого патріотизму тісно пов’язане з гуманістичним, моральним, культурним, естетичним вихованням особистості у ЗВО. Свідомий вибір такого патріотизму стає закономірним у процесі самореалізації особистості як громадянина сучасної України та носія української культурної традиції. На сьогодні становлення патріотичного світогляду молоді є складним завданням для педагогів вищої школи, оскільки протягом багатьох років патріотизм студентства формувався за пострадянською ідеологічною і формальною моделлю, нерідко «шароварною». Це спричиняло відірваність патріотичного виховання від актуальних пріоритетів життя молоді, через що не завжди вдавалося досягати високого рівня громадянської свідомості студентства, його активної включеності в суспільне життя. Натомість елітарно-дієвий патріотизм, який базується на розкритій В. Липинським у концепції «Яфетової Сили» європейськості українців, починається зі свідомої ідентифікації себе як представника талановитої й ресурсної нації, яка має багате минуле, героїчне теперішнє і перспективне майбутнє. Він мотивує молодь до суттєвого внеску в розбудову суспільства й держави як запоруку особистісного успіху та реалізації власних ідентичностей як громадянина, патріота, українця. А отже, такий тип патріотизму може бути визнаний ефективним і перспективним для повоєнного відновлення України після перемоги. Ключові слова:історія України, патріотичне виховання, елітарно-дієвий патріотизм, Яфетова Сила, яфетичність.
Виховання елітарно-дієвого патріотизму у вищій школі (на основі концепції «Яфетової Сили» В’ячеслава Липинського)